COMPARATIVE STUDY OF SELECTED PERCEPTUO- MOTOR SKILL TEST ON YOUNG MALE AND FEMALE TABLE TENNIS PLAYERS (International Journal of Food and Nutritional Sciences, 2022)
The study aimed to compare the Dutch Perceptuo-Motor Skill Test scores of young male and female table tennis players. A random sample of two hundred highly skilled national table tennis players—one hundred male and one hundred female—from various Delhi-area table tennis academies served as the study's subjects. The subjects' ages ranged from 12 to 18. Irene R. Faber et al. (2014) developed the Perceptuo-Motor Skill Test, which was used to collect the data. TThe hypothesis was tested at the 0.05 level of significance, and the data were computed using the mean, standard deviation, and "t" test. Our results indicate that the following variables are significant: Ball skill (t=0.640), agility (t=0.000), speed while dribbling (t=0.003), ball throwing (t=0.000), aiming at target (t=0.906), sprint (t=0.000), vertical jump (t=.007), and eye-hand coordination (t= 0.001). Conclusion: With the exception of ball skill and aiming at target, which were not statistically significant, male and female performance on all test battery items—agility, speed while dribbling, throwing a ball, sprinting, vertical jump, and eye-hand coordination—was significantly different.